Advancing Building and Construction Higher Education: The Online Real-Time Block Model’s Contributions to Professional Skills, Gender Equity, and Industry Preparedness - Nima Izadyar; Le Li; Shuo Chen; Darryl O’Brien (Buildings)
Traditional In-Person Semester-Length (IP-SL) courses often struggle with inherent time constraints, lack of flexibility, and geographic limitations, delaying effective learning and accessibility for students. Moreover, the extended duration of the Semester-Length (SL) structure reduce focus due to engagement with multiple subjects simultaneously, increased stress, and limited timely feedback and assessment. This study evaluates the Online Real-Time Block Model (ORT-BM), an intensive online model, highlighting its potential to enhance engagement, satisfaction, and inclusivity in project-based programs like construction in higher education. Building surveying as a critical field in construction is selected as the case study since professional surveyors must stay current with rapidly evolving building codes, regulations, and sustainability practices. However, the rigid structure of IP-SL courses often leaves graduates less prepared to meet industry needs. Conducting a comparative analysis of a case study, the Bachelor of Building Surveying program (NBBS) at Victoria University, the research compares three teaching models: IP-SL (2016–2018), In-Person Block Model (IP-BM, 2019–2020), and ORT-BM (2020–2023) using Student Evaluation of Units (SEU) data and Quality Indicators for Learning and Teaching (QILT) metrics. Findings, derived from SEU and QILT, reveal that ORT-BM improves student satisfaction, accelerates course completion rates, and fosters gender equity through inclusive learning environments while enhancing accessibility for geographically dispersed and disadvantaged students. By integrating advanced digital tools like virtual site visits, ORT-BM enhances professional readiness, aligning education with evolving industry standards. Future research may explore developing hybrid models to optimize cognitive load further, improve accessibility, and enhance flexibility.